Fragility approach for performance-based design in fluid-structure interaction problems, Part I: Wind and wind turbines, Part II: Waves and elevated coastal structures - Do, Trung Quang, author; van de Lindt, John W., advisor; Heyliger, Paul R., committee member; Mahmoud, Hussam N., committee member; Zahran, Sammy, committee member (Colorado State University. Libraries, 2016)
This dissertation focuses on a methodology for performance-based design using fragilities in fluid-structures interaction problems. Two types of fluid-structure interaction problems are investigated in this dissertation: Part I: wind-structure interaction (for wind turbine tower-base fatigue), and Part II: wave-structure interaction (for elevated coastal structures subjected to shear and uplift loading). The first problem type focuses on performance-based design of a wind turbine tower base connection subjected to wind loading using a fatigue limit state. A finite element model for wind turbines is subjected to nonlinear wind loading in the time domain. The relative motion of the actual wind speed and velocity of the moving blades in the along-wind direction creates force nonlinearity for the applied wind load, and hence, necessitates a fluid-structure interaction model. Then, a model for fatigue assessment including crack propagation was developed for the tower base connection. The inclusion of crack propagation is expected to extend the service life of the tower compared to conventional fatigue life analysis using the characteristic S-N approach. By varying the tower thickness, diameter, and considering predefined levels of crack propagation, fragility curves based on a fatigue life limit state are developed for the application of performance-based design. The desired fatigue life of a wind turbine tower for different wind sites can be obtained based on the fragilities. Finally, an illustrative example of performance-based design for a typical 5-MW wind turbine throughout Colorado is used as an illustrative example in this study. The second type of problem focuses on development of a performance-based design methodology for elevated coastal structures such as bridges and buildings. Initial numerical results are compared to existing data from a large-scale bridge section test and a full-scale transverse wood wall tested previously at the O.H. Hinsdale Wave Research Laboratory at Oregon State University. These validations provide the foundation for developing a method of wave generation for interaction with bridge and building models. By introducing fragility modeling, a variety of design options can be considered consisting of either raising the elevation of the bridge or strengthening the structure itself in order to obtain the desired probability of failure for a specified of hurricane surge and wave intensity.
Keywords: fatigue; hurricane wave and surge; wind turbine; fragility; elevated coastal structures; performance-based design